1972
DOI: 10.1093/oxfordjournals.aje.a121445
|View full text |Cite
|
Sign up to set email alerts
|

Virologic Studies of Acute Respiratory Disease in Young Adults

Abstract: Hamre, D. and M. Beem (DepL Pediatrics, Univ. of Chicago, Chicago, 111. 60637). Virologic studies of acute respiratory disease in young adults. V. Coronavirus 229E infections during six years of surveillance. Am J Epidemiol 96: 94-106, 1972.-In a surveillance study of acute respiratory disease in medical students that spanned six consecutive seasons between 1961 and 1968 and encompassed 937 student years of observation, infection with coronavirus 229E was identified by virus isolation and serologic studies. Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Previous studies have analyzed the prevalence of HCV antibodies in the sera of various populations in North America [Cavallaro and Monto, 1970;Hamre and Beem, 1972;Hendley et al, 1972;Kaye et al, 1971;McIntosh et al, 19701, South America [Candeias et al, 19721, and Europe [Bradburne and Somerset, 1972;Hovi et al, 1979;Zakstelskaya et al, 19721 and shown that HCV antibodies are widespead in these populations. Several of these reports describe variations in the incidence of antibodies to HCVs depending on a number of factors including the population studied and the season the samples were taken.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have analyzed the prevalence of HCV antibodies in the sera of various populations in North America [Cavallaro and Monto, 1970;Hamre and Beem, 1972;Hendley et al, 1972;Kaye et al, 1971;McIntosh et al, 19701, South America [Candeias et al, 19721, and Europe [Bradburne and Somerset, 1972;Hovi et al, 1979;Zakstelskaya et al, 19721 and shown that HCV antibodies are widespead in these populations. Several of these reports describe variations in the incidence of antibodies to HCVs depending on a number of factors including the population studied and the season the samples were taken.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have suggested that these viruses may be associated with more severe diseases, and in particular gastroenteritis, but as yet there is no clear evidence to support this [Macnaughton and Davies, 19811. Several reports have analyzed the extent of infections in various populations in America and Europe by estimates of HCV antibodies in sera from patients and volunteers [Bradburne and Somerset, 1972;Candeias et al, 1970;Cavallaro and Monto, 1970;Hamre and Beem, 1972;Hendley et al, 1972;Hovi et al, 1979; Kaye et al, 1971;McIntosh et al, 1970;Zakstelskaya et al, 19721. A number of assays have been used, including neutralization, complement fixation, hemagglutination inhibition, and radioimmunoassay.…”
Section: Introductionmentioning
confidence: 99%
“…The techniques that generally have been employed are complement fixation (CF) and hemagglutination inhibition (HI) (2,3). However, certain problems of sensitivity and specificity are inherent in these methods and difficulty in interpretation of results can sometimes be resolved only by use of the far more complicated neutralization test (2,4,5).…”
mentioning
confidence: 99%
“…Coronaviruses have been shown in several seroepidemiologic studies to be not uncommon in both pédiatrie and adult populations (18,19,38,40,48,53,61,62,75) but, in spite of this, recovery of these agents has been quite rare, as only thirty-two isolations have been reported since 1965 when the first strain, B814, was recovered in human embryonic trachea! organ culture (HETOC) by Tyrrell and Bynoe (15, 38, 45, 68,80,81).…”
Section: Detection Of Coronavirus Strain 692mentioning
confidence: 99%